Circulating cytokines reflect the expression of pro-inflammatory cytokines in atherosclerotic plaques. Issue 2 (August 2015) - Edsfeldt, Andreas; Grufman, Helena; Asciutto, Giuseppe; Nitulescu, Mihaela; Persson, Ana; Nilsson, Marie; Nilsson, Jan; Gonçalves, Isabel
Abstract: Aims: Inflammation is a key factor in the development of plaque rupture and acute cardiovascular events. Although imaging techniques can be used to identify vulnerable atherosclerotic plaques, we are lacking non-invasive methods, such as plasma markers of plaque inflammation that could help to identify presence of vulnerable plaques. The aim of the present study was to investigate whether increased plasma levels of pro-inflammatory cytokines reflects inflammatory activity within atherosclerotic plaques. Methods and results: Cytokines were measured using Luminex immunoassay in 200 homogenized plaque extracts and plasma, obtained from 197 subjects undergoing carotid surgery. Plasma levels of macrophage inflammatory protein-1β (MIP-1β), tumor necrosis factor- α (TNF-α) and fractalkine correlated significantly, not only with plaque levels of the same cytokines but also with the abundance of several pro-inflammatory and atherogenic cytokines assessed in plaque tissue. High plasma levels (upper tertile) of MIP-1β, TNF-α and fractalkine identified the presence of a plaque with high inflammation (above median of a score based on the plaque content of MIP-1β, TNF-α, interferon-γ (IFN-γ) and fractalkine) with a sensitivity between 65 and 67% and a specificity between 78 and 83%. Furthermore, this study shows that high plasma levels of MIP-1β, TNF-α and fractalkine predict future transient ischemic attacks. Conclusions: Our findings show that the plasma levels of MIP-1β, TNF-α and fractalkine reflect the levels of several pro-atherogenic cytokines in plaque tissue and might be possible plasma markers for a vulnerable atherosclerotic disease. We thereby propose that these cytokines can be used as surrogate markers for the identification of patients with high-risk plaques. Highlights: Plasma levels of inflammatory cytokines are associated with plaque levels of cytokines. Plasma levels of MIP-1β, TNF-α and fractalkine could be used to identify atherosclerotic plaques with high inflammatory activity. Plasma levels of MIP-1β, TNF-α and fractalkine predicts future cerebrovascular event.